Peningkatan Status Kebersihan Gigi Melalui Home Visit Pada Balita Lheu Blang - Suryani, Linda; Cut Ratna Keumala; Sisca Mardelita; Eka Sri Rahayu (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Public dental health, especially in children, really needs to be considered, because childhood is very susceptible to dental and oral diseases. Dental nursing care carried out by dental nurses is aimed at improving the degree of dental health. The role of the family by motivate children to get used to maintaining dental hygiene. Community service aims to improve the status of dental and oral hygiene through home visits to toddlers in Lheu Blang village, Aceh Besar. This community service is carried out using a descriptive method, with the target of 30 children under five in Lheu Blang village. The intervention is a visit to a toddler's house by providing guidance, direction, demonstration, and training children to brush their teeth properly and correctly. The results obtained that the dental and oral hygiene status of toddlers before the intervention was in the very bad category (53.3%), and the results after the intervention were in a good category (66.7%). The conclusion is that there is an increase in the status of dental hygiene in the good category (66.7%). Suggestions that children under five are able to brush their teeth properly and correctly and on time. Keywords: Dental Hygiene Status, Home Visit, Toddler